The story that cannot be told - Kramer, J. Kasper (Atheneum Books for Young Readers, 2019)
Ten-year-old aspiring writer Ileana is sent to live with her grandparents after her uncle Andrei disappears for criticizing Romania's communist government in 1989. Away from the secret police and spies, Ileana, a lover of stories and folklore, tries to find her own voice and write her own story as she tries to save the village she now calls home.